Structural and Functional Characterization of Fibronectin in Extracellular Vesicles From Hepatocytes - Li, Xinlei; Chen, Ruju; Kemper, Sherri; Brigstock, David R. (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EVs) are membrane-limited nanoparticles that are liberated by cells and contain a complex molecular payload comprising proteins, microRNA, RNAs, and lipids. EVs may be taken up by other cells resulting in their phenotypic or functional reprogramming. In the liver, EVs produced by non-injured hepatocytes are involved in the maintenance of hepatic homeostasis or therapeutic outcomes following injury while EVs produced by damaged hepatocytes may drive or exacerbate liver injury. In this study, we examined the contribution of EV fibronectin (FN1) to the biogenesis, release, uptake, and action of hepatocyte-derived EVs. While FN1 is classically viewed as a component of the extracellular matrix that regulates processes such as cell adhesion, differentiation, and wound healing and can exist in cell-associated or soluble plasma forms, we report that FN1 is also a constituent of hepatocyte EVs that functions in EV uptake by target cells such as hepatocytes and hepatic stellate cells (HSC). FN1 co-purified with EVs when EVs were enriched from conditioned medium of human or mouse hepatocytes and a direct association between FN1 and hepatocyte EVs was established by immunoprecipitation and proteinase protection. FN1 ablation in mouse hepatocytes using CRISPR-Cas9 did not alter EV biogenesis but EV uptake by HSC was significantly reduced for FN1 knockout EVs (EVΔFN1) as compared to EVs from wild type hepatocytes (EVWT). The uptake by hepatocytes or HSC of either EVWT or EVΔFN1 required clathrin- and caveolin-mediated endocytosis, cholesterol, lysosomal acidic lipase activity, and low pH, while macropinocytosis was also involved in EVΔFN1 uptake in HSC. Despite their differences in rate and mechanisms of uptake, EVΔFN1 functioned comparably to EVWT in ameliorating CCl4-induced hepatic fibrosis in mice. In conclusion, FN1 is a constituent of hepatocyte EVs that facilitates EV uptake by target cells but is dispensable for EV-mediated anti-fibrotic activity in vivo.